Potential Determinants of Clostridium Spp. Occurrence in Polish Silage - Goldsztejn, Magdalena (J Vet Res, 2020)
INTRODUCTION: Silage quality deteriorates with Clostridium spp. contamination, and if consumed, such silage jeopardises herd health and productivity. Minimising its occurrence reduces economic and animal welfare risks. The study investigated the influence of environmental and technological determinants on the Clostridium genus’ occurrence in silage. MATERIAL AND METHODS: Analyses were conducted on 305 silage samples directly collected from farms located in all Polish provinces. Cultures and isolates were evaluated phenotypically and examined for occurrence of Clostridium spp., particularly C. perfringens and C. botulinum using PCR techniques. The results were statistically analysed using the ᵡ(2) test for continuous and Student’s t-test for non-continuous values. RESULTS: The most influential effect on Clostridium spp. occurrence is exerted by factors potentially associated with primary production, like the type of fertilisation and the contamination level of the ensiled feed material. Clostridium spp. was detected in 232 (76%) samples, and C. perfringens strains, predominantly toxinotype A, in 79 (26%). C. botulinum occurrence was not detected. CONCLUSIONS: Deterioration of silage by clostridia could be prevented by a properly conducted ensiling process with the addition of starter cultures, but the presence of spores mainly depends on primary production and the extent of contamination of the feed material.